Strategic Thinking Skills and Personality Style of Media Managers - Azarpour, Samaneh (Nordic Journal of Media Management, 2021)
Purpose: The aim of current research is to find out whether it will be possible to select the right person for manager position with the skill of strategic thinking, by testing the personality type of candidate in the media companies. Methodology: The data of this research collected by questionnaires that distributed among 221 managers of Iranian journals located in Tehran. For testing our hypotheses and statistical analysis of relationships among different dimensions of strategic thinking and personality of managers, SPSS and LISRE Software have been employed. Findings/Contribution: The results show that there is meaningful relationship between the variables.